The Influence of Intrinsic and Extrinsic Motivation on Employee Performance : The Mediating Role of Mission Commitment at BPJS Ketenagakerjaan - Faizal Rachman; Hapzi Ali (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study explores the influence of intrinsic and extrinsic motivation on employee performance, with mission commitment serving as a mediating variable in a public sector institution. A quantitative method was employed, gathering data through structured questionnaires completed by 100 employees at BPJS Ketenagakerjaan. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3.0. Results indicate that intrinsic motivation significantly influences both mission commitment and employee performance, whereas extrinsic motivation only significantly affects performance. Furthermore, mission commitment mediates the relationship between both forms of motivation and performance. These findings underscore the importance of cultivating internal drive and value alignment to improve public sector performance.